Analysis of the Influence of Principal's Managerial Competence and Organizational Climate on Teacher Performance with Teacher Commitment in Public Senior High Schools in Tuban Regency - Maimun Muhibbuddin, Mohammad; Wahyudin, Agus; Oktarina, Nina (Educational Management, 2025)
This study examines the impact of principal’s managerial competence and organizational climate on teacher performance, with teacher commitment as a moderating variable. Using a quantitative correlational approach, data were collected through surveys involving teachers at public senior high schools in Tuban Regency and analyzed using inferential statistics. The results show that both managerial competence and organizational climate positively influence teacher performance, directly and indirectly through teacher commitment. High levels of teacher commitment strengthen these relationships, indicating that schools led by competent principals and with supportive climates foster more committed and high-performing teachers. The study concludes that improving teacher performance requires not only effective leadership and a positive work environment but also efforts to increase teacher commitment. Educational policies should thus target principal development, organizational climate enhancement, and strategies that foster greater dedication among teachers to optimize educational outcomes.